Research Trends and Hotspots of Extracorporeal Membrane Oxygenation: A 10-Year Bibliometric Study and Visualization Analysis - Wang, Huaqin; Deng, Siqi; Fan, Xiaoyu; Li, Jinxiu; Tang, Li; Li, Yamin; Yu, Bo (Frontiers in Medicine, 2021)
To determine the research hotspots and trends in the field of extracorporeal membrane oxygenation (ECMO), and to provide a reference for further and wider research in the future.